Development of Flipbook-Based Learning Media Using the Dick & Carey Model and Its Impact on Elementary School Students’ Creative Problem-Solving Skills - Yasni, Zainul; Djono; Maulidina, Rizqiya C Wanda; Santoso, Fatan Alim; Agustin, Ika Wahyu (Universitas Sebelas Maret, 2025)
The development of educational technology encourages the use of interactive digital media capable of delivering multimodal and adaptive learning. This study aims to develop Flipbook Maker-based learning media with the Dick & Carey instructional design model and analysed its effectiveness in improving elementary school students' problem-solving creativity. The development was carried out through the stages of needs analysis, design, production, formative evaluation, revision, and summative evaluation. This study used a modified Research and Development (R&D) approach involving expert validation, individual trials, small group trials, and field tests. The problem-solving creativity instrument was compiled based on indicators of fluency, flexibility, originality, and elaboration. The results showed that the flipbook obtained a